Exploring air pollution awareness: insights from interviews with technology enthusiasts using wearable monitoring devices - Bernasconi, Sara; Angelucci, Alessandra; Canali, Stefano; Aliverti, Andrea (Frontiers in Public Health, 2024)
This study aims to investigate shifts in awareness regarding air pollution and its correlation with interest in using wearable devices for air quality monitoring. 16 healthy participants, predominantly engineers, residing or studying in Milan, were interviewed to assess their knowledge and interest in air pollution. Participants then walked a predefined route of 4.5 km in Milan while observing real-time air pollution data recorded by a wrist-worn wearable device. Post-walk interviews explored changes in awareness and enthusiasm for personal air quality monitoring. Results indicated widespread recognition of pollution sources, including industries, transportation, and agricultural activities, and health effects. Interestingly, reliance on sensory cues for air quality evaluation was prevalent among participants, underscoring a potential bias toward olfactory indicators. Despite interest in personal air quality monitoring, concerns regarding continuous monitoring leading to feelings of powerlessness and mental stress were noted. Nevertheless, participants expressed interest in actionable information to mitigate these concerns and promote lifestyle choices to decrease exposure to pollutants. Notably, a shift in awareness was observed following interaction with the monitoring device, indicating its potential to enhance public awareness and support for air quality policies. Findings underscore the importance of technological interventions in promoting public awareness and understanding of air pollution dynamics.